Seizure Frequencies and Number of Anti-epileptic Drugs as Risk Factors for Sudden Unexpected Death in Epilepsy - Ryu, Han Uk; Hong, Jin Pyo; Han, Su-Hyun; Choi, Eun Ju; Song, Ji Hyun; Lee, Sang-Ahm; Kang, Joong Koo (Journal of Korean medical science, 2015)
The purpose of this study was to investigate the association between clinical variables and sudden unexpected death in epilepsy (SUDEP) and identify risk factors for SUDEP. SUDEP is one of the most frequent causes of death in patients with epilepsy. Previous studies have reported possible risk factors associated with SUDEP, but there need to be elucidated yet. The cases were 26 patients with SUDEP and three control patients were included for each case, matched for age, sex, and date of initial clinical visit. All demographic and clinical characteristics, including age, sex, disease duration, classification of epilepsy, age at seizure onset, kind and number of antiepileptic drugs, were compared between cases and controls. Seizure frequency was higher in SUDEP cases than in controls (P=0.035). Univariate analysis using conditional logistic regression showed that higher seizure frequency (odds ratio [OR]=3.1, P=0.021) and the number of antiepileptic drugs (AEDs) (OR=2.0, P=0.009) were significantly associated with SUDEP. Only the number of AEDs remained significant in multivariate analysis (OR=1.8, P=0.026). Frequent seizures and multi-drug therapy were associated with SUDEP. This may suggest that the severity of epilepsy is associated with SUDEP, regardless of the type of AED used.